Effects of learning approaches, locus of control, socio-economic status and self-efficacy on academic achievement: a Turkish perspective - Suphi, Nilgün; Yaratan, Hüseyin (Routledge, 2012)
In this study the effects of learning approaches, locus of control (LOC), socio-economic status and self-efficacy on undergraduate students in North Cyprus was investigated. Four questionnaires were administered on 99 students in order to collect data regarding the learning approaches, LOC, self-efficacy and demographic factors. High cumulative grade point average and self-efficacy were shown to be an indicator of academic achievement and high self-efficacy was related to the use of deep approach (DA). Students, whose mothers had lower levels of education, were found to also predict academic success. No direct significant relationship between DA and academic achievement was found.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: academic achievement, self-efficacy, learning approaches, socio-economic status, locus of control,; MOTIVATION, SUCCESS, STUDENTS, EXPECTANCIES, BEHAVIOR, EDUCATION & EDUCATIONAL RESEARCH; Educational Attainment, Correlation, Cognitive Style, Foreign Countries, Grade Point Average, Self Efficacy, Learning, Socioeconomic factors